Why are firms with more managerial ownership worth less? - Fabisik, Kornelia; Fahlenbrach, Rüdiger; Stulz, René M.; Taillard, Jérôme P. (Journal of Financial Economics, 2021)
Using more than 50,000 firm-years from 1988 to 2015, we show that the empirical relation between a firm's Tobin's q and managerial ownership is systematically negative. When we restrict our sample to larger firms, as in the prior literature, we confirm earlier findings of an increasing and concave relation between q and managerial ownership. We show that cumulative past performance and liquidity can explain these seemingly contradictory results. Better performing firms have more liquid equity, which enables firms and insiders to more easily sell shares after the IPO, and they also have a higher Tobin's q.